A Computational Analysis of Aberrant Delay Discounting in Psychiatric Disorders - Story, Giles W.; Moutoussis, Michael; Dolan, Raymond J. (Frontiers in Psychology, 2016)
Impatience for reward is a facet of many psychiatric disorders. We draw attention to a growing literature finding greater discounting of delayed reward, an important aspect of impatience, across a range of psychiatric disorders. We propose these findings are best understood by considering the goals and motivation for discounting future reward. We characterise these as arising from either the opportunity costs of waiting or the uncertainty associated with delayed reward. We link specific instances of higher discounting in psychiatric disorder to heightened subjective estimates of either of these factors. We propose these costs are learned and represented based either on a flexible cognitive model of the world, or an accumulation of previous experience, or through evolutionary specification. Any of these can be considered suboptimal for the individual if the resulting behaviour results in impairments in personal and social functioning and/or in distress. By considering the neurochemical and neuroanatomical implementation of these processes, we illustrate how this approach can in principle unite social, psychological and biological conceptions of impulsive choice.